Company Law - Siti Salwa Jaafar, author 629008; Marliana Jamaluddin, author 629009 (Shah Alam, Selangor : Oxford Fajar, 2018)
The Companies Act 2016 came into effect on 31 January 2017, repealing the Companies Act 1965. The new Act contains numerous major changes, including the company constitution, abolishment of the authorized capital concept, annual reporting and general meetings, directorships, and the corporate rescue mechanism. To date, there are not many textbooks that specifically cover the 2016 Act and, thus, this publication is a good reference material for students. This book is ideal for all commerce students pursuing Diploma in Accounting at polytechnics in Malaysia. It covers the relevant topics in corporation law within seven chapters and is structured based on the company law syllabus in Malaysian polytechnics. Each chapter opens with Learning Outcomes and at the end of each chapter, students are provided with a summary, a list of key terms, and structured and discussion questions. Apart from polytechnic students, university students and the general public may also find the book useful.